Manajemen Program Penguatan Pendidikan Karakter Melalui Pembelajaran Daring dan Luring di Masa Pandemi Covid 19-New Normal - Hartati, Niken Sri; Thahir, Andi; Fauzan, Ahmad (El-Idare, 2020)
The purpose of this study was to understand the management of strengthening character education through online and offline learning during the Covid 19 New Normal pandemic which includes planning, implementation and evaluation. The research method used a qualitative descriptive method through observation, documentation and interviews at MTs Hidayatul Islamiyah Bandar Lampung. Data were analyzed using the following steps: data reduction, display data, and conclusion / verification). The results of this study indicate that first, planning to strengthen student character education has been carried out properly through the preparation of objectives, strategies and policy mapping as well as procedure mapping and program refinement using RPP designs; second, the implementation of character education runs well through activities of a religious nature, planting nationalism, social care and concern for the environment; third, evaluation of the management of the strengthening of character education of students through monitoring activities on the implementation of activities by carrying out reflection, analysis and follow-up plans.